2005
DOI: 10.1002/bit.20789
|View full text |Cite
|
Sign up to set email alerts
|

The cold‐shock response in cultured mammalian cells: Harnessing the response for the improvement of recombinant protein production

Abstract: There are a growing number of reports on the sub-physiological temperature culturing (<37 degrees C) of mammalian cells for increased recombinant protein yield, although the effect is variable between cell lines, expression systems, and the product of interest. What is becoming clear is that exposing mammalian cells to sub-physiological temperatures invokes a coordinated cellular response involving modulation of the cell cycle, metabolism, transcription, translation, and the cell cytoskeleton. Opportunities cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
112
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(120 citation statements)
references
References 59 publications
5
112
3
Order By: Relevance
“…It has been proven that it is an active response and cells synthesize specific cold inducible proteins (Kondo et al 1992;Holland et al 1993;Jones and Inouye 1994;Derry et al 1995;Nishiyama et al 1997a, b;Kaufmann et al 1999;Danno et al 2000;Sonna et al 2002;Dresios et al 2005;Yoon et al 2006;Baik et al 2006;Al-Fageeh et al 2006). A change in the phosphorylation patterns at the tyrosine residues of two proteins (~180 and 80 kDa) was also observed following reduction of the culture temperature providing further proof that there is an active signalling response to mild hypothermia in CHO (Kaufmann et al 1999).…”
Section: The Use Of Cell Cycle Arrest To Increase Recombinant Proteinmentioning
confidence: 88%
See 3 more Smart Citations
“…It has been proven that it is an active response and cells synthesize specific cold inducible proteins (Kondo et al 1992;Holland et al 1993;Jones and Inouye 1994;Derry et al 1995;Nishiyama et al 1997a, b;Kaufmann et al 1999;Danno et al 2000;Sonna et al 2002;Dresios et al 2005;Yoon et al 2006;Baik et al 2006;Al-Fageeh et al 2006). A change in the phosphorylation patterns at the tyrosine residues of two proteins (~180 and 80 kDa) was also observed following reduction of the culture temperature providing further proof that there is an active signalling response to mild hypothermia in CHO (Kaufmann et al 1999).…”
Section: The Use Of Cell Cycle Arrest To Increase Recombinant Proteinmentioning
confidence: 88%
“…The quality of recombinant products, with regard to isoform pattern, sialic acid content, and in vivo biological activity, is maintained at reduced temperatures (Yoon et al 2003b;Clark et al 2004;Bollati-Fogolin et al 2005). The mechanism whereby cells at lower temperatures improve productivity is still poorly understood although recent studies have demonstrated that reduced culture temperature invokes a coordi- nated response involving the cell cycle, transcription and translational machinery, and the arrangement of the cytoskeleton (Chuppa et al 1997;Moore et al 1997;Ohsuye 1998, 1999;Jorjani and Ozturk 1999;Hendrick et al 2001;Yoon et al 2003b;Fox et al 2004Fox et al , 2005Baik et al 2006;Al-Fageeh et al 2006). Low culture temperature results in reduced metabolism (glucose/medium consumption, oxygen uptake, lactate production and ammonia production) and shear sensitivity which leads to delayed initiation of apoptosis and helps in extending the duration of the stationary/production phase (Moore et al 1997;Chuppa et al 1997;Ohsuye 1998, 1999;Jorjani and Ozturk 1999;Hendrick et al 2001;Yoon et al 2003a, b;Trummer et al 2006;Wong et al 2006).…”
Section: The Use Of Cell Cycle Arrest To Increase Recombinant Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…Other possibilities, including manipulation of the temperature for example, could also enhance production. Low temperature appears to hold promise for enhancing protein expression yields in mammalian cells (Al-Fageeh et al 2006;Wulhfard et al 2008). Nonetheless, the production of rSSL as a secreted product in a eukaryotic expression system might remain difficult as a result of its function.…”
Section: Discussionmentioning
confidence: 99%